The Role of Islam Nusantara and Religious Moderation - Siti Wardah Rizkiyah; Kelin Kelin; Ijum Setiawan; Hapipi Hapipi (International Research and Development for Human Beings (IRDH), 2024)
Islam Nusantara can be characterized as a distinctive and empirical manifestation of Islam that has emerged in Indonesia through interactions, localization, adaptation, translation, and assimilation of local social, cultural, and literary elements. This study utilizes a literature review with the objective of examining the interpretation of Islam Nusantara and its correlation with Religious Moderation within the present context of Indonesia. Islam Nusantara represents a concept that embodies religious moderation in Indonesia, demonstrating a balanced approach that is neither radical nor liberal in its ideology. It encourages the nurturing of indigenous knowledge that holds social, cultural values, and promotes religious tolerance.